Maternal infection and stress during pregnancy and depressive symptoms in adolescent offspring. (November 2017) - Murphy, Shannon K.; Fineberg, Anna M.; Maxwell, Seth D.; Alloy, Lauren B.; Zimmermann, Lauren; Krigbaum, Nickilou Y.; Cohn, Barbara A.; Drabick, Deborah A.G.; Ellman, Lauren M.
Abstract: Maternal infection during pregnancy has been linked to increased risk of offspring depression. Additionally, maternal stress during pregnancy has been consistently linked with adverse offspring outcomes associated with depression. Relatedly, stress has been associated with increased risk of infection; however no study has investigated stress-infection interactions during pregnancy and risk for offspring depression. Participants were drawn from the Child Health and Development Studies (CHDS), a prospective, longitudinal study that enrolled pregnant women from 1959 to 1966. Maternal health and birth outcome information were collected, as well as open-ended interviews about worrisome events during pregnancy. The present study included participants from a subsample of women whose offspring (n = 1711) completed self-reports of depressive symptoms during adolescence. Results indicated that maternal infection during only the second trimester was associated with higher scores on adolescent offspring depressive symptoms, while controlling for maternal education at birth, adolescent age, and maternal depressive symptoms at adolescence. Maternal experiences of daily stress during pregnancy moderated this association, such that mothers diagnosed with second trimester infection and who experienced daily stress had offspring with significantly higher depression scores than mothers of adolescents diagnosed with an infection alone. Findings have potential implications for prevention and intervention strategies. Highlights: Second trimester prenatal infection may contribute to depressive symptoms in offspring. Prenatal stress moderates the association between maternal infection and depression. Results have implications for prevention and intervention strategies.